2018
DOI: 10.1242/dev.169102
|View full text |Cite
|
Sign up to set email alerts
|

Kmt2b conveys monovalent and bivalent H3K4me3 in mouse spermatogonial stem cells at germline and embryonic promoters

Abstract: The mammalian male germline is sustained by a pool of spermatogonial stem cells (SSCs) that can transmit both genetic and epigenetic information to offspring. However, the mechanisms underlying epigenetic transmission remain unclear. The histone methyltransferase Kmt2b is highly expressed in SSCs and is required for the SSC-to-progenitor transition. At the stem-cell stage, Kmt2b catalyzes H3K4me3 at bivalent H3K27me3-marked promoters as well as at promoters of a new class of genes lacking H3K27me3, which we ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…In our study, we discovered that CBX8 recruits KMT2b to the LGR5 promoter to maintain H3K4me3 modification status, implying that KMT2b potentially functions in tumorigenesis and tumor progression. Moreover, in stem cells, the classic function of KMT2b is to attach H3K4me3 to bivalent promoters with the aid of PRC1 component [15]; Interestingly, we found that the promoter of LGR5 which accumulated H3K4me3 and H3K27me3 was bivalent promoter. In addition, CBX8 is also a component of PRC1 complex.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our study, we discovered that CBX8 recruits KMT2b to the LGR5 promoter to maintain H3K4me3 modification status, implying that KMT2b potentially functions in tumorigenesis and tumor progression. Moreover, in stem cells, the classic function of KMT2b is to attach H3K4me3 to bivalent promoters with the aid of PRC1 component [15]; Interestingly, we found that the promoter of LGR5 which accumulated H3K4me3 and H3K27me3 was bivalent promoter. In addition, CBX8 is also a component of PRC1 complex.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have reported that CBX proteins function in cooperation with other proteins to promote epigenetic activation or silencing of gene expression [13, 14]. As Set1/Trithorax-type H3K4 methyltransferases catalyze H3K4 methylation [15], we utilized an RNA interference (RNAi) screening approach to identify potential H3K4 modifiers responsible for LGR5 regulation. Notably, depletion of KMT2b, but not other enzymes, decreased LGR5 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify a novel factor involved in spermatogenesis, we focused on the genes targeted by KMT2B and upregulated during spermiogenesis (Tomizawa et al, 2018). To this end, we reanalyzed data previously obtained from cultured germline stem cells (GSCs) with chromatin immunoprecipitation followed by sequencing (ChIP-seq) and RNA-sequencing (RNA-seq) (Tomizawa et al, 2018).…”
Section: Tsga8 Is Targeted By Kmt2b and Is Specifically Activated In Spermatidsmentioning
confidence: 99%
“…Because the testis is the organ that expresses the largest number of genes of all organs in mice (Kimmins and Sassone-Corsi, 2005;Xia et al, 2020), the roles of the vast majority of the genes expressed during spermiogenesis for morphological remodeling remain unknown. We recently showed that a small subset of genes that are upregulated during spermiogenesis are potentially programmed for expression in undifferentiated spermatogonia by histone H3 lysine 4 trimethylation (H3K4me3) (Tomizawa et al, 2018). Chromatin priming and later activation is a phenomenon suggested in other systems such as pluripotent stem cells and macrophages (Glass and Natoli, 2016;Harikumar and Meshorer, 2015).…”
Section: Introductionmentioning
confidence: 99%